2017
DOI: 10.1002/jcp.25907
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits RANKL‐induced osteoclastogenesis and bone resorption in vitro and prevents LPS‐induced bone loss in vivo

Abstract: Osteoclasts are multinuclear giant cells responsible for bone resorption in lytic bone diseases such as osteoporosis, arthritis, periodontitis, and bone tumors. Due to the severe side-effects caused by the currently available drugs, a continuous search for novel bone-protective therapies is essential. Artesunate (Art), the water-soluble derivative of artemisinin has been investigated owing to its anti-malarial properties. However, its effects in osteoclastogenesishave not yet been reported. In this study, Art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Song et al showed that eriodictyol was potentially useful for the prevention of osteoporosis through inhibiting osteoclast formation and function . Achyranthes bidentata polysaccharide, berberine sulphate, nitidine chloride, artesunate and so on were also found to be potential therapeutic candidates for the prevention or treatment of osteoporosis . Other studies also investigated the osteoporotic effects of compounds such as magnolol and polysaccharides …”
Section: Discussionmentioning
confidence: 99%
“…Song et al showed that eriodictyol was potentially useful for the prevention of osteoporosis through inhibiting osteoclast formation and function . Achyranthes bidentata polysaccharide, berberine sulphate, nitidine chloride, artesunate and so on were also found to be potential therapeutic candidates for the prevention or treatment of osteoporosis . Other studies also investigated the osteoporotic effects of compounds such as magnolol and polysaccharides …”
Section: Discussionmentioning
confidence: 99%
“…Mice bone marrow–derived macrophages (BMMs) were collected and cultured as described by Wei . Briefly, C57 BL/6 male mice were killed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…We induced OC differentiation as previously described . BMMs were cultivated in α‐MEM supplemented with 30 ng/mL of M‐CSF, 10% FBS, and 100 ng/mL of RANKL.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies have been proven that many plants, such as artesunate [37] and picrasidine I [38] are helpful for lytic bone disease treatment. Mon is a alkaloid derived from the seeds of the crotalaria spectabilis plant, has a therapeutic effect on cancers,such as skin cancer and cervical cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, high dose (60 mg/kg) of Mon can induce hypertension in animals via receiving an intraperitoneal injection after 21 days [17]. However, Mon was merely injected over the local calvarium with 2 mg/kg or 5mg/kg every two days for 7 days in this study, according to previous report [37]. Importantly, to detect the potential side effects of Mon in our study, the pathological examination of liver, kidney and spleen have been done, and the results showed that Mon had no effect on them (Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%